Metarhizium species in soil from Brazilian biomes: a study of diversity, distribution, and association with natural and agricultural environments. (October 2019) - Riguetti Zanardo Botelho, Ana Beatriz; Alves-Pereira, Alessandro; Colonhez Prado, Rafaela; Zucchi, Maria Imaculada; Delalibera Júnior, Italo
Abstract: Metarhizium is a diverse genus of fungi adapted for different ecologies, including soil saprotrophs, entomopathogens, and endophytes. We characterized the genetic diversity and distribution of Metarhizium species in soils found in native and agricultural landscapes within Brazilian biomes (Amazon, Cerrado, Atlantic Forest, Caatinga, and Pampa). Current species limits were determined with 5′-TEF, and the genetic diversity discerned using MzIGS3 sequences. Metarhizium robertsii, Metarhizium anisopliae, Metarhizium pingshaense, and three other lineages that lie beyond currently recognized species were found. Only soils from the Amazon contained all the species. The diversity of Metarhizium species associated with native vegetation was greater than that identified in annual and perennial crops. M. robertsii was the most abundant species (65%), followed by Metarhizium sp. indet. 1, which exhibited the highest haplotype and nucleotide diversities. Metarhizium sp. indet. 3 was found predominantly in the Caatinga biome. This information increases the knowledge about diversity and belowground species composition of Metarhizium in Brazil. Highlights: Soils from Brazilian biomes harbor a high genetic diversity of Metarhizium spp. Metarhizium diversity was higher in soils from native than in agricultural areas. Amazon was the only biome that presented haplotypes of all six Metarhizium spp. A new lineage was found predominantly in the dry Caatinga biome. Metarhizium sp. indet. 1 presented the highest haplotype and nucleotide diversities.